Analisis Produk Domestik Regional Bruto Kawasan Gerbangkertosusila Provinsi Jawa Timur - Muchtolifah; Sishadiyati; Karenina, Silvia (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The purpose of this study is to find out the effect of investment, HDI, labor, and inflation on gross regional domestic product (PDRB) in districts/cities incorporated in the Gerbangkertosusila area. Observation data was obtained from BPS East Java Province and East Java Provincial Investment Office with time series 2010-2019. Data analysis methods use multiple linear regressions. The result is known that in all districts / cities free variables consisting of investment, HDI, labor, and inflation together have a positive influence on the bound variable, namely PDRB. Keywords: investment, HDI, labor, inflation, GRD. The investment variables of Mojokerto Regency and Surabaya City have a positive and significant effect on the PDRB. Lamongan Regency investment variables have a negative and significanteffect on the PDRB, investment variables in other districts / cities do not have a significant effecton the PDRB. IPM variables in all districts / cities have a positive and significant effect on PDRB. Lamongan Regency labor variables have a negative and significant effect on PDRB, while labor variables in other districts / cities do not have a significant effect on PDRB. Inflation variables have a significant influence on the PDRB of Surabaya City.